Dr. Jimmy Smith at Meet EBC with Tefera Gedamu - Smith, Jimmy W. (Ethiopian Broadcast Corporation (EBC), 2014)
A conversation with Dr. Jimmy Smith, Director General of ILRI- By Tefera Gedamu : Meet EBC